Stress Management, Spiritual Growth, and Workplace Well-Being Among the Employees of a Selected University in the Philippines - Castillo, Sheryll Ann M.; Parinas, Sabina L.; Narbarte, Reuel E. (8ISC Abstract Proceedings, 2022)
The well-being of employees is a key factor in determining an organization's long-term effectiveness as a direct link between productivity levels and the general health and well-being of the workforce have been shown in several studies. Employees’ well-being can play a critical role in the life of organizations; hence, it is important to periodically assess employees’ well-being. This study aimed to determine the level of the employees’ workplace well-being and to assess whether stress management and spiritual growth relate to the well-being of the employees. Using descriptive correlational design and random sampling techniques, 164 university employees participated in an online survey via the Google form. Anchored on the five components of well-being, namely positive emotions, engagement, relationships, meaning, and accomplishment (PERMA), a 23-item Workplace Well-being Scale, using a 10-point Likert response scale with eight dimensions, has been adopted in this study. Findings show that employees have very good stress management skills (M = 4.09± 0.62), a high level of spiritual growth (M = 4.14± 0.58), and a high level of workplace well-being (M = 7.78± 0.93). Further, regression analysis show that stress management (β = .393, t = 5.466, p <.001) and spiritual growth (β = .286, t = 3.984, p < .001) are statistically significant positive predictors of workplace wellbeing accounting for 33.8% (r2 change = .338, p = <.001) of the variance in the workplace wellbeing. Results are useful to further enhance workplace well-being such that the university may devise systems that foster good relationships and engagement, as well as programs for stress reduction techniques that are behavioral in nature. It would be relevant for the next study to explore the workplace experiences, challenges, and coping strategies to understand better workplace wellbeing. Keywords : workplace, well-being, coping strategies, stress management